Analysis of Heavy Metals in Shellfish in Tanjung Balai Waters - Reny Yuliana Siahaan; Jansen Silalahi; Zulkifli Lubis (Institute for Halal Industry and System (IHIS) Universitas Gadjah Mada, 2022)
Abstract: Shellfish is a source of toxic heavy metals and the maximum levels of heavy metals allowed in shellfish by BPOM RI are Lead 1.5 mg/kg, Cadmium 1 mg/kg and Copper 20 mg/kg. Heavy metal content in shellfish is influenced by environmental pollution in which the shellfish live. The purpose of this study was to determine the levels of heavy metals in three types of shellfish in Tanjung Balai Asahan waters. Shellfish samples were taken from 3 different locations in Tanjung Balai in July 2021. Determination of the levels of heavy metals Pb, Cd and Cu in green mussels, mussels and blood clams was carried out using the AAS method with atomic absorption spectrophotometer. The results showed the levels of lead (Pb), cadmium (Cd) and copper (Cu) in Green mussels in Tanjung Balai, namely: Pb of 0.273 mg/kg – 0.406 mg/kg, Cd of 0.089 mg/kg – 0.106 mg/kg mg /kg, Cu is 1,864 mg/kg – 2,011 mg/kg. In oyster shells Pb was 0.051 – 0.095 mg/kg, Cd was 0.077 – 0.091 mg/kg, and Cu was 1.024 mg/kg – 1.064 mg/kg. It was concluded that green mussels had the highest heavy metal content. The levels of heavy metals in the analyzed shellfish samples were still below the maximum levels permitted by BPOM RI. Keywords: Lead, Cadmium, Copper,Atomic Absorption Spectrophotometry, Shells